Coenzyme Q10 effect on semen parameters: Profound or meagre?. (9th April 2020) - Vishvkarma, Rahul; Alahmar, Ahmed T.; Gupta, Gopal; Rajender, Singh
Abstract: Coenzyme Q10 has shown promise in treating male infertility; however, there are inconsistencies across the published data. We undertook a quantitative meta‐analysis by pooling data from three placebo‐controlled randomised clinical trials (RCTs) in order to evaluate the efficacy of CoQ10 in improving semen parameters. Sperm count, sperm motility, sperm forward motility, sperm morphology and CoQ10 level in the seminal plasma were measured and quantitatively correlated with CoQ10 oral administration. Pooled analysis showed a significant impact of CoQ10 in improving sperm motility and forward motility, without a significant impact on sperm count, sperm morphology, ejaculate volume or seminal plasma level of CoQ10. Efficacy assessment suggested that CoQ10 shows better results at higher doses and when administered for a period of more than 3 months but not longer than 6 months. We conclude that CoQ10 has a profound effect on sperm motility and a meagre effect on all other parameters. Therefore, CoQ10 can be used for treating asthenozoospermic infertility with the dosage and duration depending upon the severity of the disorder and the patient's response to the treatment.